2022
DOI: 10.1177/10778004221134088
|View full text |Cite
|
Sign up to set email alerts
|

A Good Name: Pseudonyms in Research

Abstract: People’s names and the places, animals, and items named by people are deeply personal and reflective of their culture and identity, yet in qualitative research, the standard is to use pseudonyms. This practice is thought to protect research participants, but when are “real” names most respectful and appropriate? How might researchers include research participants in these considerations? The purpose of this methodological article is to increase transparency and collaboration around the participant naming proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Participants’ ages ranged from 36 to 47 years ( Table 1 ). Pseudonyms were used to describe the participants to protect the identity of the participants and because the sample was demographically similar ( 40 ). The majority of mothers were hesitant about COVID-19 vaccines, and their hesitancy was driven by the unfamiliarity and novelty of the vaccine, balancing the risks and benefits of the vaccine, distrust in government, science, and public health authorities, decreased trust in pediatricians and increased trust in medical specialists.…”
Section: Resultsmentioning
confidence: 99%
“…Participants’ ages ranged from 36 to 47 years ( Table 1 ). Pseudonyms were used to describe the participants to protect the identity of the participants and because the sample was demographically similar ( 40 ). The majority of mothers were hesitant about COVID-19 vaccines, and their hesitancy was driven by the unfamiliarity and novelty of the vaccine, balancing the risks and benefits of the vaccine, distrust in government, science, and public health authorities, decreased trust in pediatricians and increased trust in medical specialists.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in line with our ethical obligations, we took measures to safeguard their social and economic well-being during and after the fieldwork. Studies have demonstrated that ensuring anonymity for informants in qualitative studies not only fosters trust between researchers and participants but also encourages informants to share their experiences without fear of repercussions related to the research topic [11,12]. Since most participating surgeons voluntarily engaged in our research within state-owned hospitals and held academic positions, our study posed no threat to their well-being.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…I have come to appreciate that naming is a balance between considerations of anonymity, relational ethics with participants and organizations (see Lahman et al, 2022), and a need to include rich descriptions of context. And it does not matter if generic labels are assigned, pseudonyms are used, or real names are kept in, as Guenther (2009) stated, "the act of naming is an act of power" (p. 412).…”
Section: Being Mindful Of Names 11mentioning
confidence: 99%